Intestinal Malrotation in a Suspected Celiac Disease Patient: A Case Report - Romero-Velez, Gustavo; Rivas, Yolanda; Prasad Burjonrappa, Sathya (Journal of Surgery Proceedings, 2018)
Intestinal malrotation is the incomplete rotation of the midgut during embryogenesis. The reported prevalence is 1 in 500 live births, however some studies report a prevalence as high as 1% of the population1, 2. Traditionally it is though as a disease of the pediatric population presenting as bilious emesis during the first year of life but can present with different symptoms even in adulthood. Presentation in older populations tends to be atypical, chronic abdominal pain, nausea and diarrhea being the most commonly reported symptoms 3. However, as these symptoms accompany almost all-gastrointestinal pathology it is difficult to determine if abnormalities of rotation and fixation of the intestine are the cause for the symptoms in a given patient given its relative rarity. It therefore is important to have a high index of suspicion in patients with non-specific gastrointestinal symptoms. We report laparoscopic management of a patient with abnormal rotation/fixation who was treated for many years as celiac disease (CD). Celiac disease is an immune mediated systemic disorder elicited by gluten in genetically susceptible individuals4. It can present as chronic abdominal pain, chronic diarrhea, failure to thrive, weight loss, stunted growth, distention and fatigue. His symptoms immediately resolved after surgery.
Keywords: Intestinal Malrotation; Celiac Disease; Chronic Abdominal Pain; Laparoscopic Management; Midgut Rotation; Case Report